7th International Conference on Higher Education Advances (HEAd'21) 2021
DOI: 10.4995/head21.2021.12939
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Behaviours in using Learning Resources in Higher Education: How do behaviours reflect success in Programming Education?

Abstract: Programming education traditionally has been an important part of Information Technology-related degrees but, more recently, it is also becoming essential in many STEM domains as well. Despite this, drop-out rates in programming courses in higher education institutions are considerable and cannot be ignored. At the same time, analysing learning behaviours has been reported to be an effective way to support the improvement of teaching and learning quality. This article aims to deliver an in-depth analysis of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(10 reference statements)
2
4
0
Order By: Relevance
“…The quiz formative activity is the online activity where high-performing students contributed the most in programming courses and non-programing courses. This behaviour of having high contributions to formative activities such as quizzes in coding is consistent with the studies that high-performing students in programming education have been consistently active in practice as their study progresses (Hassinen & Mäyrä, 2006;Mai et al, 2021;Pedrosa et al, 2016).…”
Section: Online Engagementsupporting
confidence: 89%
See 1 more Smart Citation
“…The quiz formative activity is the online activity where high-performing students contributed the most in programming courses and non-programing courses. This behaviour of having high contributions to formative activities such as quizzes in coding is consistent with the studies that high-performing students in programming education have been consistently active in practice as their study progresses (Hassinen & Mäyrä, 2006;Mai et al, 2021;Pedrosa et al, 2016).…”
Section: Online Engagementsupporting
confidence: 89%
“…Studies have shown a positive relationship between student motivation and academic achievement (Pintrich & De Groot, 1990). It has also been indicated that high-achieving students show a refined ability to select and modify study behaviors (Mai et al, 2021), manage their time and use more effective study strategies (Dunlosky et al, 2013) and routinely engage in and adapt skills to pursue these behaviors (Zimmerman & Schunk, 2001). Despite evidence of the association between high performance and effective study behaviors as a primary study strategy, Persky (2018) found in his longitudinal study that high-achieving students relied on re-reading texts and re-watching videos.…”
Section: High-performing Studentsmentioning
confidence: 99%
“…From RMT, eigenvalues falling outside of are assumed to deviate from its expected predictions [ 63 , 64 ]. Hence, we can use this theory to test the reliability of the relationships in our empirical data [ 65 ].…”
Section: Research Methodologymentioning
confidence: 99%
“…It has been noticed [ 18 , 59 ] that, in practical usage of the online learning system, students tend to interact sporadically with course material items. This phenomenon appears to create noise in the data and may limit the chance of detecting the difference in learning behaviours among students.…”
Section: Methodsmentioning
confidence: 99%